The Meaning of Sign in Political Advertising of the Indonesian Presidential Election - Hartanto, Arief (Jurnal Pekommas, 2021)
Political advertising is part of a political campaign used by presidential and vice-presidential candidates for taking voters a voice. Every political advertising is produced that creates a certain meaning through a sign or symbol which contains a message from presidential and vice-presidential candidates. Message in political advertising can describe the image of candidate pairs of leadership candidates with the appropriate character and related to the issues they want to build. This research is qualitative research using semiotic analysis. The object of research is the political advertising of the presidential and vice-presidential candidate pair Jokowi Amin in 2019. This political advertising was taken from the social media account of Youtube KPU-RI. This paper was aimed to conduct an analysis of signs in Jokowi Amin political advertising in the 2019 election and to find out the political advertising category in the positive or negative advertising. Jokowi, who is a presidential candidate and incumbent that has a special strategy for created political advertising used in his campaign. Overall, political advertising Jokowi Amin has a communication style that features several signs as his trademark and is in a positive category.